PEMBANGUNAN EKONOMI ISLAM BERBASIS KOMUNITAS - Fredly Alfarraby; Khansa Hasna Nurhaliza; Najuwa Aurel Annisa (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
The economic sector is one indicator of the development of a country. The economy in a country cannot only be supported by the government of that country. Community organizations are also needed to support community economic activities. Several community organizations in the fields of education and religion, such as Islamic Boarding Schools, Nahdlatul Ulama, and Muhammadiyah, in their journey can become strategic supporters in carrying out developments in the ummah's economic sector. Along the way, there have been several attempts that have been made by these three organizations in pursuing the economic growth of the community, but not least in the recent results, which are still below expectations. Educational and religious organizations, such as Muhammadiyah, Nahdlatul Ulama, and Islamic boarding schools are basically non-profit oriented organizations that have the ability to create socio-economic welfare as well as develop the potential of existing human resources. This description contains the programs and policies that have been carried out by these three organizations in relation to the economic development and empowerment of the Indonesian people. Through the programs and policies of these three organizations, it is hoped that they will be able to create support from the community as well as improve the economic welfare of the Indonesian people.